2021
DOI: 10.1038/s41598-021-88297-2
|View full text |Cite
|
Sign up to set email alerts
|

Side-group-mediated thermoelectric properties of anthracene single-molecule junction with anchoring groups

Abstract: Charge transfer characteristics of single-molecule junctions at the nanoscale, and consequently, their thermoelectric properties can be dramatically tuned by chemical or conformational modification of side groups or anchoring groups. In this study, we used density functional theory (DFT) combined with the non-equilibrium Green’s function (NEGF) formalism in the linear response regime to examine the thermoelectric properties of a side-group-mediated anthracene molecule coupled to gold (Au) electrodes via anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…In this study we used the thiol anchoring unit to mediate the coupling of the PDT and BPDT molecules to the FM cobalt electrodes. However, it was previously shown that the electron donating/accepting character of anchoring units can modify the conductance of singlemolecule junctions by the energy-level line up relative to the Fermi energy of electrodes [48][49][50], ultimately resulting in an enhanced/suppressed conductance depending on the nature of the molecular structure [51,52]. Furthermore, here we used unperturbed PDT and BPDT molecules as the central molecule in the MTJ.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In this study we used the thiol anchoring unit to mediate the coupling of the PDT and BPDT molecules to the FM cobalt electrodes. However, it was previously shown that the electron donating/accepting character of anchoring units can modify the conductance of singlemolecule junctions by the energy-level line up relative to the Fermi energy of electrodes [48][49][50], ultimately resulting in an enhanced/suppressed conductance depending on the nature of the molecular structure [51,52]. Furthermore, here we used unperturbed PDT and BPDT molecules as the central molecule in the MTJ.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, here we used unperturbed PDT and BPDT molecules as the central molecule in the MTJ. However, functionalization of the molecule with side groups can also have dramatic modulatory effects on the conductance of the system by reorganization of the frontier molecular orbitals relative to the Fermi energy level of the electrodes [52,53]. These modifications can favorably or unfavorably tune the behavior of the voltage-dependent plasticity of effective conductance in MTJ which certainly deserves further examination.…”
Section: Plos Onementioning
confidence: 99%
“…Previously, several studies explored the effect of structural or chemical modification on the thermoelectric properties of molecular junctions by manipulating their transport properties. For example, it has been shown that the length of the molecule [14][15][16][17], functionalization of the molecule with side groups [18][19][20][21], intervention of anchoring groups [22][23][24], molecule-electrode coupling geometry [25,26] and impurity doping [7,27] can significantly tune the conductance, thermopower and figure of merit of molecular junctions, depending on the system. In this context, a key factor in the regulation of transport properties of metal-molecule-metal structures is the energy level alignment between Frontier molecular orbitals (FMOs) and the Fermi level of electrodes [28,29] that can be modulated, e.g., by the geometric position or charge transfer nature of anchoring groups [24,30,31] or side groups [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Perturbation of molecular systems with side groups in various positions can similarly modify the thermoelectric properties of the system [18][19][20][21]. The chemical character or the position of side groups can be a determinant of charge polarization between molecule and the electrodes due to the realignment of the FMOs relative to the Fermi energy of the electrodes [21,36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation